Effective Mobilization Prevents Risk Of Decubitus Occurrence In Bed Rest Patients In Icu Room RSUD dr. Doris Sylvanus Palangka Raya - Suryagustina Suryagustina; Yusak Kaharap; Rimba Aprianti (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background: Pressed wounds (decubitus) are serious problems that often occur in patients with impaired mobility, such as stroke patients, spinal fractures or degenerative diseases. As a result of the above, the occurrence of decubitus can also increase the duration of hospital stay or LOS (length of stay) so that this will increase the burden, especially the cost of hospitalization will increase with length of stay in the hospital.Objective: The purpose of this study aims to determine the effect of mobilization of the incidence of decubitus in bed rest patients in the ICU hospital room dr. Doris Sylvanus Palangka Raya.Methods: The research design used was pre experimental with pre-post test design in a group (One-group pre-post test design), with sampling technique used Consecutive Sampling. Patients treated in ICU hospital room dr. Doris Sylvanus Palangka Raya is 18 people. Data collection was done by observation.Results: Study obtained p value is 0,000 Î± 0.05 which means there is influence on the incidence of decubitus in bed rest patients in the ICU hospitals dr. Doris Sylvanus Palangka Raya.Conclusion: Effective mobilizationreduces the risk of Decubitusin bed rest patient. Expected nurses and other healt personel in providing nursing care, especially in the preparation of intervention and implement the implementation to prevent the occurrence of decubitus.Keywords: ICU, Bed Rest, Decubitus, Mobilization.